Implementasi Good Governance dalam Pengelolaan Wakaf Lembaga: Studi Kasus pada Lembaga LKAF Sidogiri - Saiful Bakhri (Idarotuna : Journal of Administrative Science, 2025)
The purpose of this study is to examine how the Sidogiri Financial and Charitable Institution (LKAF) manages a sharia-based waqf using good governance principles. Waqf has strategic potential for the community's economic growth, especially if it is managed effectively and professionally. However, issues such a lack of accountability, professionalism, and openness continue to plague Indonesian waqf administration methods. Using semi-structured interviews with the head of the LKAF fundraising division and a literature case study, this study employs a qualitative descriptive methodology. The study's findings demonstrate how LKAF has put good governance concepts into practice through frequent reporting, internal audits, expert training, and adherence to state and Sharia laws. Drilled wells and flagship initiatives like the Thousand Waqf Program show how to maximize waqf assets, which directly affect community welfare. The digitalization of reporting and external audits still presents difficulties, nevertheless. These results show that the efficacy of Sharia-based waqf management in Indonesia can be enhanced by the regular application of good governance principles.